AN INTELLIGENT PHARMACY AND HEALTH CARE SERVICES - G, Nandini; K, Anitha (The journal of contemporary issues in business and government, 2021)
This paper delineates the model of the All Time Medication and Health device for the use of every person needing prescriptions or clinical assistance. ATMAH incorporates a customized prescription treats machine to allot steadies as indicated by an authority's cure. The circulating framework is constrained by the raspberry pi which is a lone board PC and its second piece is the online section for a customer to check his medications, and for the pro to make an prescriptions. The device allocates out the prescribed prescriptions by the authority when the customer affirmations of patients are endorsed from the database. The online passage depends on two fronts - a page and an android application which are associated with a comparable database. The patient can see his nuances likewise, cures through the android application or site page by marking in with legitimate accreditations.